AB0053 Increased Frequency of Plasmacytoid Dentritic Cells in Rheumatoid Arthritis Patients in Response to IL-6R Blockade. (10th June 2014) - Pers, Y.-M.; Quentin, J.; Le Blay, P.; Jorgensen, C.; Louis-Plence, P.
Abstract : Background: Dendritic cells (DCs) are professional antigen-presenting cells (APCs) that can induce either immunity or tolerance. Myeloid DCs (mDCs) and plasmacytoid DCs (pDCs) represent the 2 major subsets of DCs, with human pDCs defined as CD4 + CD11c - CD123 hiCD1c- CD303 +HLADR+ cells, and mDCs defined as CD4 + CD1c +CD123lo CD303 - CD45RO - HLADR + cells. Some studies reported that patients with therapy-induced remission of rheumatoid arthritis (RA) exhibited higher numbers of circulating pDCs. Objectives: Indeed, in vivo effects of IL-6 inhibition on DCs are partially unknown. Tocilizumab (TCZ) is the first therapeutic agent targeting IL-6 to be effective in RA. Our aim was to monitor the changes in circulating mDCs and pDCs during TCZ therapy in patients with RA. Methods: DC subsets were characterized by flow cytometry in the peripheral blood of patients with RA (n=15) and in healthy volunteers (n=10). In patients with RA, these levels were measured before and during TCZ therapy (8 mg/kg every 4 weeks). Response to TCZ therapy was evaluated at 12 weeks. All the patients fulfilled the 1987 ACR criteria for RA. At baseline, the mean DAS28 score was 5.2 (±1.3). At 3 months, 9 patients were classified as responders (DAS28 1.8±0.8) and 6 patients were classified as non-responders (DAS28 4.0±0.4). Statistical analyses were performed by Mann-Whitney U tests or Wilcoxon signed-rank tests. Results: At baseline, patients with active RA were characterized by a significantly decrease frequency of circulating pDCs compared to healthy donors (40.2% vs 60.9%; p<0.01). After 3 months of TCZ therapy, pDC frequency has not changed (48.5% vs 40.2%) while mDC frequency decrease significantly (31.1% vs 22.3%; p<0.05). Moreover, TCZ-treated patients who reached low disease activity at Week 12 had significant increase frequency of pDC (52.0% vs 38.7%; p<0.05) as compared with non-responders patients (43.2% vs 42.5%). Conclusions: Our study reveals an increased frequency of circulating pDC in responder patients to TCZ therapy. We previously demonstrated that the clinical response was also associated with increased frequencies of CD39 + Treg cells. Our results suggest a crosstalk between DC and Tregs to restore/induce tolerance. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4336